Pengaruh Kepemimpinan Transformasional, Motivasi Intrinsik dan Disiplin Kerja terhadap Produktivitas Karyawan - Adeta Suci Anggraini; Devia Wulandari; Camelia Oktariani Setiawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of transformational leadership, intrinsic motivation, and work discipline on employee productivity. A quantitative approach was used with a sample of 30 employees selected through purposive sampling. Data were collected through questionnaires and analyzed using Statistical Package for the Social Sciences (SPSS). The results show that transformational leadership, intrinsic motivation, and work discipline have a positive and significant impact on employee productivity. These findings indicate that improving leadership quality, fostering intrinsic motivation, and enhancing employee discipline can collectively increase overall productivity. This study provides insights for organizations to enhance managerial effectiveness and human resource management.